How Staff of Youth Programs Respond to Culture-Related Incidents: Nonengagement Versus Going "Full-Right-In". (January 2017) - Gutiérrez, Vanessa; Larson, Reed W.; Raffaelli, Marcela; Fernandez, Mariela; Guzman, Sandy
Incidents in which program leaders confront issues of culture and race occur regularly in many youth programs. These incidents are important because they reflect powerful dimensions of youth's lived experience and bring issues of injustice and program inclusiveness to the fore. This study examined these culture-related incidents and how leaders responded to them. Interviews were conducted with 50 leaders from 27 programs serving primarily Latino, African American, and European youth. Half the programs served middle school–aged teens and half high school–aged teens. Qualitative analyses identified four categories of incidents, each presenting distinct considerations for leaders. Two ( offensive remarks and discrimination ) involved inappropriate speech and unjust actions. Two ( discomfort with intercultural contact and cultural identification and identity ) involved youth's expression of negative attitudes toward others' or own group. Leaders differed in their responses to incidents. A universalist, race-blind group asserted that culture did not matter in their program and reported virtually no incidents. A second group reported culture-related incidents but described limited responses because they lacked confidence or skills. A third group appeared to represent best practices: These leaders engaged directly with the incidents and facilitated reflective dialogue in which youth drew on experiences, analyzed situations, and learned through collective discussion. Implications for practice are drawn.